2017
DOI: 10.5057/ijae.ijae-d-16-00045
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Background Objects on Unpleasantness Evoked by Lotus-seed-pods-on-the-living-body Images (“Hasu-colla”)

Abstract: Abstract:The photomontage of lotus seedpods on human skin has been called "Hasu-colla" in Japan, and this can elicit strong aversion in viewers. Previous studies have reported that lotus seedpods evoke core disgust, and that Hasu-colla relates to animal reminder disgust. However, the relationship between unpleasantness evoked by lotus seedpods and that by Hasu-colla has not been demonstrated. The present study investigated whether Hasu-colla evokes stronger disgust than lotus seedpods presented alone as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
1
10
1
Order By: Relevance
“…Yamada and Sasaki (2017) also showed that individuals with previous skin-related medical problems reported higher discomfort ratings towards trypophobic images compared to those who have no history of skin disease. Two other recent studies found greater unpleasantness ratings for faces of humans and animals when a trypophobic image (lotus seedpod) was superimposed on them compared to the trypophobic image viewed in isolation or when viewing the trypophobic image on inverted faces (Furuno et al, 2017;2018). While the evidence seems to support the infectious disease / disgust response, previous work assumes excess energy at mid-range spatial frequencies to be the primary reason for visual discomfort, and our results show otherwise.…”
Section: Discussioncontrasting
confidence: 67%
“…Yamada and Sasaki (2017) also showed that individuals with previous skin-related medical problems reported higher discomfort ratings towards trypophobic images compared to those who have no history of skin disease. Two other recent studies found greater unpleasantness ratings for faces of humans and animals when a trypophobic image (lotus seedpod) was superimposed on them compared to the trypophobic image viewed in isolation or when viewing the trypophobic image on inverted faces (Furuno et al, 2017;2018). While the evidence seems to support the infectious disease / disgust response, previous work assumes excess energy at mid-range spatial frequencies to be the primary reason for visual discomfort, and our results show otherwise.…”
Section: Discussioncontrasting
confidence: 67%
“…Further, our results can be at least partly explained by the hypothesis that the disgust to the clusters of dots is caused by the reminder of disease and contamination ( Furuno et al., 2017 ; Kupfer & Le, 2018 ; Rozin, Haidt, & McCauley, 2008 ; Skaggs, 2014 ; Wada, 2012 , 2016 ; Yamada & Sasaki, 2017 ). Our results were consistent with the previous study suggesting that disgust to the clusters on the skin was stronger than dots on the nonskin objects, such as wood grain ( Wada, 2016 ) and stones ( Furuno et al., 2017 ). We did not see any signs of ceiling effect: The average disgust rating to the upright and inverted faces, with and without dots, was around 5 to 6 points of the 9 points.…”
Section: Discussionmentioning
confidence: 65%
“…Some researchers have hypothesized that disgust to the clusters of dots increases when they are presented on human skin because they remind us of scars and sores ( Skaggs, 2014 ). This hypothesis was supported by a study in which viewers reported greater disgust when a cluster of dots was placed on faces rather than on stones ( Furuno, Imaizumi, Maeda, Hibino, & Koyama, 2017 ). In addition, a study by Kupfer and Le (2018) reported that disgust to a cluster was stronger when the cluster consisted of disease-relevant elements such as circular rash marks on a chest than those consisting of disease-irrelevant elements such as drilled holes in a brick wall.…”
Section: Introductionmentioning
confidence: 79%
“…Researchers explain that observers experience discomfort from trypophobic objects in order to rapidly avoid them because most poisonous animals have a similar pattern on their surface [ 1 ]. Another explanation is based on the notion that patterns of trypophobic objects are similar to scars and sores [ 2 , 3 ]. Such visual information is associated with animal reminder disgust, which is a subclass of the emotion of disgust, and is linked with primitive fears of animals, including humans, regarding death and body damage [ 4 ].…”
Section: Introductionmentioning
confidence: 99%